Rural-urban migratión in Bolivia: Advantages and disadvantages - Lykke E. Andersen (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2002)
This paper discusses the advantages and disadvantages of rural-urban migration, and shows that the costs of increased urbanization (crime, pollution, congestion, etc) in Bolivia are rather small compared to the costs experienced in other Latin American countries. The benefits, on the other hand, may be large. Encouraging rural-urban migration may be one of the cheapest ways of reducing poverty in Bolivia because it is so much cheaper to provide basic services like electricity, piped water, schools, and health services to people when they are gathered in towns or cities. In addition, economies of scale in the cities bring economic opportunities and increase people's income.
Keywords: 330